Efeito da adição de resíduos de um sistema de cultivo em aleias sobre os pools de fósforo e de matéria orgânica - Dadalto, Danúbia Lemes (2013)
The objective of this study was to evaluate the effect of adding waste from a system of cultivation in alleys on the pools of phosphorus and organic matter in the soil, in addition to investigate the dynamics of P fractions in the soil and discuss their relationship with availability for cultures. The study was carried out in the experimental area of ​​the State University of Maranhão - UEMA, in São Luís – MA, in an alley cultivation system. The samples of Soil was removed at depths 0-10 cm and 10-20 cm in the treatment plots: Acacia + Gliricidia; Acacia + Leucena; Sombrero + Gliricidia; Sombrero + Leucena; Leucena + Gliricidia. A no-residue treatment (SR) and a control (no fertilization and no residue). P and MO fractionations were carried out. THE addition of residues from an alley cropping system altered the dynamics of phosphorus and organic matter in the soil, in addition to improving the chemical properties of the soil. However, the addition of residues did not cause changes in the occluded P fraction, which highlights the accumulation of P in the most labile compartments, so P is found in less stable forms, of greater availability for purchasing plants. P-NaHCO3 had a higher amount of P in the labile reservoir than the P-resin fraction, highlighting the importance of this fraction in this system. The input of residues from an alley cultivation system did not guarantee the accumulation of P organic. More studies need to be carried out to ensure full understanding of the absence of organic P. The MO fractions were mainly influenced by the difference between the amounts of deposited waste and the C/N ratio of the combinations, this demonstrates the need for a constant supply of organic material to maintain adequate levels of C stock in the soil.